INOVASI TEKNOLOGI DALAM E-BISNIS: SOLUSI UNTUK EFISIENSI ENERGI DAN PENGURANGAN EMISI KARBON - Nabila, Nabila; Zhafira, Zhafira; Sumarni, Endang (Jurnal Inspirasi Ilmu Manajemen, 2025)
This article discusses the role of technological innovation in e-business as a solution for energy efficiency and carbon emission reduction, focusing on the implementation of various environmentally friendly technologies that can enhance the operational sustainability of companies. This research aims to analyze the impact of technologies such as Internet of Things (IoT)-based energy management systems, big data analytics, and cloud computing on reducing energy consumption and carbon footprints of companies. The methodology used is a qualitative approach with in-depth analysis of various case studies in the e-business sector that have successfully implemented green technologies. The findings indicate that the adoption of environmentally friendly technologies not only benefits the environment but also enhances operational efficiency and significantly reduces energy costs. With collaboration between government, private sector, and communities, the e-business sector can play a crucial role in global efforts against climate change.